(untitled) (European Journal of Pure and Applied Mathematics, 2010)
Let X and Y be Banach spaces and L(X,Y) be the space of all bounded linear operators from X to Y.Â If X = Y, we write L(X) forL(X,Y).Let X Y be the tensor product of X and Y , and X Y be the completion of XY with respect to a uniform cross norm. In this paper, we present an extension of the Hille-Yosida Theorem to tensor product semigroups.